What Does the Literature Suggest About Coretax, Digital Literacy, Service Quality, and Tax Compliance Costs? - Irma Nurul Husna; Sekar Mayangsari (Summa : Journal of Accounting and Tax, 2026)
Tax compliance costs represent a significant economic burden for taxpayers in fulfilling their tax obligations. The digital transformation of tax administration through the Coretax system, along with improvements in digital literacy and service quality, is often associated with reduced compliance costs; however, existing empirical evidence remains fragmented and is frequently examined in isolation. This study aims to synthesize the existing literature by analyzing how these three factors are jointly discussed in relation to tax compliance costs. This study employs a Systematic Literature Review (SLR) approach, following a structured protocol adapted from the PRISMA guidelines. Data were collected from Scopus, ProQuest, Garuda, Google Scholar, and SINTA using predefines keywords and inclusion stages, resulting in 32 relevant articles published between 2017 and 2026. A basic quality assessment was also conducted to ensure the relevance and reliability of the selected studies. The finding indicate that the Coretax consistently demonstrates the potential to reduce compliance costs through automation, data integration, and administrative afficiency, despite challenges during the initial implementation phase. Digital literacy significantly influences taxpayer’s ability to utilize digital systems effectively, while service quality enhances user experience and reduces administrative burdens. Overall, reducing compliance costs requires not only technological advancement but alsa user readiness and institutional support through an integrated approach.